Estandarización del sistema de documentación de vinculación de la facultad de Ciencias de la Ingeniería y Aplicadas. - Chipantaxi Tufiño, Grace Joseth (2023)
At the Faculty of Engineering and Applied Sciences (CIYA) of the Technical University of Cotopaxi, as an integral part of the students' educational process, Societal engagement is required in accordance with the academic standards issued by the Council of Higher Education (CES), where students must carry out Preprofessional Practices, encompassing Work Practices, Community Service Practices, Validation of Extracurricular Activities, and/or Teaching Assistantships. The objective was to standardize the documentary system through the characterization of the Engagement processes. For standardization, the Deming cycle was employed, developed according to the established specific objectives. Firstly, the documents were characterized to determine the sequence and integration among the actors involved, using process flowcharts. Then, through non-structured interviews, the current formats within the Engagement process were collected to later create a verification check-list. Once the documentation was obtained, continued with the review and analysis of the portfolios of a group of students from previous academic periods in the CIYA Faculty. In the second stage of the cycle, the obtained documentation and parameters for modification were standardized, leading to the third stage of verification through functionality testing of the developed office resources. This was done through a satisfaction survey directed at a group of students. In the penultimate stage, modifications were made based on the satisfaction survey, along with the creation of instructions for managing the resources used for the standardization of documents, with the purpose of improving the development of the Preprofessional Practices process in the CIYA Faculty. Finally, it was concluded that with the completion of this investigative project, approximately 50% of the time dedicated to each document was minimized.